2020
DOI: 10.1029/2020gl087609
|View full text |Cite
|
Sign up to set email alerts
|

Four Atmospheric Circulation Regimes Over the North Pacific and Their Relationship to California Precipitation on Daily to Seasonal Timescales

Abstract: Precipitation in California is highly variable and not well forecasted on subseasonal‐to‐seasonal (S2S) timescales. Understanding relationships between synoptic‐scale atmospheric circulation and hydrometeorological extremes could improve predictability. This work demonstrates the importance of four North Pacific circulation regimes (called the NP4 modes) in modulating precipitation, flooding, and water resources in California. Here we demonstrate how, on daily timescales, interactions between the NP4 modes dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…Higher pressure (lower pressure) in north‐central (node 11) and subtropical eastern pacific (node 18) was associated with higher (lower) SLP in node 22 (Figures 5c and 5d), while the signs of the relationship between SLP in the west Indian ocean (node 1) and node 22 were opposite (Figure 5e). Higher pressure in node 11 was suggested to be a factor for steering the wet winter air masses away from CA (Cvijanovic et al., 2017; Guirguis et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher pressure (lower pressure) in north‐central (node 11) and subtropical eastern pacific (node 18) was associated with higher (lower) SLP in node 22 (Figures 5c and 5d), while the signs of the relationship between SLP in the west Indian ocean (node 1) and node 22 were opposite (Figure 5e). Higher pressure in node 11 was suggested to be a factor for steering the wet winter air masses away from CA (Cvijanovic et al., 2017; Guirguis et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of CMIP6 model causal networks also confirmed the strong teleconnection between node 22 SLP and CA precipitation (passing a binomial test at a 95% confidence level). Over node 22, the west coast higher pressure pushes storm tracks away from CA, resulting in anomalously drier winters (Choi et al., 2016; Cvijanovic et al., 2017; Seager et al., 2015, 2017), while lower pressure is robustly associated with wetter winters (Guirguis et al., 2020; Seager et al., 2015). Over the central‐southern CA, both observation and the majority of CMIP6 models (13 out of 18) agreed on the secondary control of northeastern pacific region (node 18) SLP on CA precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Guirguis et al. (2018, 2020) identified similar circulation modes that have >70% of concurrence with ARs that make landfall over Northern California/Pacific Northwest, and they also highlighted the importance of these modes in driving hydrologic extremes across time scales. In light of this information, we name EOF3 the “CPM.” The power spectrum density of PC3 (Figure 2c) suggests that in general the mode is indistinguishable from red noise, though it exceeds the 95% confidence line at around 70–80 days and at ∼120 days.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, while being much less prominent for total variation of Z500, PC3 is more important for California precipitation than other leading modes of variability. Guirguis et al (2018Guirguis et al ( , 2020 identified similar circulation modes that have >70% of concurrence with ARs that make landfall over Northern California/Pacific Northwest, and they also highlighted the importance of these modes in driving hydrologic extremes across time scales. In light of this information, we name EOF3 the "CPM."…”
Section: The Cpm and Its Connection To California Mean Precipitationmentioning
confidence: 87%
“…Figure 1c shows the collective in uence of the four modes, where we see that together these modes explain 25-90% variance in the portion of the domain most relevant for west coast weather. The NP4 dataset used in this study is described in Guirguis et al (2020b) and is available at https://doi.org/10.6075/J0154FJJ.…”
Section: North Paci C Atmospheric Circulation Regimesmentioning
confidence: 99%